Analysis of Two-phase Flow Field and Oil Injection Lubrication Characteristics of High-speed Gears - Shi Dong; Zhang Yuzhe; Zhang Hong; Hou Xiangying (Jixie chuandong)
The complex flow field in the high-speed gearbox affects the transmission efficiency and performance of the transmission system by affecting the gear oil injection lubrication characteristics. Therefore, it is necessary to carry out research on the two-phase flow field and lubrication characteristics of high-speed gear oil injection considering the complex flow field of high-speed gear box and the baffle structure. Based on the computational fluid dynamics method, a two-phase flow field analysis model of high-speed helical gear oil injection lubrication is established, and the two-phase flow field distribution characteristics are analyzed. On this basis, the effects of injection parameters such as injection speed, injection angle, axial injection angle, and gear baffle on the injection lubrication characteristics are further studied. The results show that the oil on the surface of high-speed helical gear inclines to one side. By increasing the injection speed or adding the positive axial angle, the oil deflection and the lubrication effect can be improved. The gear baffle plays a role in guiding the oil, and the setting of axial baffle is conducive to increasing the oil on the tooth surface. This study provides a basis for the study of two-phase flow field distribution characteristics of high-speed gearboxes and the optimization design of oil injection lubrication.